Shooting Down Military Aircraft: Pakistan Responsibilities Over India - Dewa Gede Sudika Mangku; Jilal Aqli (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: The act of firing on two Indian military aircraft carried out by Pakistan indeed constitutes the right of air control over military aircraft according to the Paris Convention of 1919 and the Chicago Convention of 1944, according to which this convention's control rights over foreign military aircraft are strict and maximum, it does not contain exceptions Article 32 of the Paris Convention and Article 3 (c) of the 1944 Chicago Convention The right of maximum and strict control of the state over its airspace is only directed to military aircraft of other countries, where the consideration of national security is the main reason. But still, the shooting action carried out by Pakistan against Indian military aircraft is an act of negligence on airspace which became its sovereignty, due to the lack of coordination related to the shootings carried out.Purpose/Objective Study: This study aims to determine and understand the regulation of Indian military aircraft in the 1944 Chicago Convention on Flight of Military Aircraft to Airspace in Other Countries and the responsibility of the state of Pakistan in firing Indian military aircraft from the perspective of international air law.Design/Methodology/Approach: This research is research that uses normative legal research methods using a type of legislation approach and case approach. The legal materials used are primary, secondary, and tertiary legal materials that are useful for obtaining conclusions that are relevant to the problems in this study.Findings: The results showed that: 1) the regulation of Indian military aircraft in the 1944 Chicago Convention was categorized as a military aircraft (state aircraft) type of MiG-21 Bison interceptor which was indeed used for military, police and customs purposes, which in this case did not have the right to do flight above the airspace of another country before obtaining permission in advance from the country concerned; 2) the form of responsibility that must be given is in the form of termination of acts, apologies and remedial actions in the form of restitution, ie repairing as before the Indian military aircraft that he shot and providing protection for pilots he captures, this is as regulated in Article 31 of the ILC Draft.Paper Type: Research Article